Perceptions of Teachers at SDN 104202 Bandar Setia Regarding the Effectiveness of Smart Boards in Teaching English as a Foreign Language - Afrida Damai Yanti Siregar; Michaela Gracia Hutabarat; Putri Marsya; Sri Ayuning Melati; Nurmayani N; Ivana Septia Rahaya (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to explore teachers' perceptions of the effectiveness of smart boards in teaching English as a foreign language at the elementary school level. The background highlights the availability of smart boards in schools and the importance of understanding how teachers perceive their usability, benefits, and challenges. A qualitative descriptive approach was employed, involving interviews with teachers, classroom observations, and literature studies. The research was conducted at SDN 104202, located on Jalan Terusan Dusun V, Bandar Setia Village. Data collection was carried out in a short period without spanning multiple days. The findings reveal that smart boards facilitate the presentation of multimedia materials such as videos and PowerPoint slides, which enhance student engagement and visual understanding. However, teachers reported technical constraints, limited training, and the fact that the technology does not inherently shift traditional teacher-centered practices. The study implies that the successful integration of smart boards requires not only infrastructure but also sustained pedagogical support and professional development.